Multi-critical points in black hole phase transitions - Masoumeh Tavakoli; Jerry Wu; Robert B. Mann (Journal of High Energy Physics, 2022)
Abstract We present the first examples in black hole thermodynamics of multicritical phase transitions, in which more than three distinct black hole phases merge at a critical point. Working in the context of non-linear electrodynamics, we explicitly present examples of black hole quadruple and quintuple points, and demonstrate how n-tuple critical points can be obtained. Our results indicate that black holes can have multiple phases beyond the three types observed so far, resembling the behaviour of multicomponent chemical systems. We discuss the interpretation of our results in the context of the Gibbs Phase Rule.